Discourse Approach to Creating Educational Situations for Pre-school Age Children - Belinova, Natalia V. (International Journal of Psychosocial Rehabilitation, 2020)
The paper deals with topical problems of the modern discourse terminology and specifics of creating the educational discourse for children of preschool age. The paper discusses the modern interpretation of discourse and the possibility of its use as a formal component in the educational frame. The paper tries to apply a discourse approach to development and organization of educational situations for children of preschool age, such as specially organized thematic activities, performances, literary performances, quizzes, competitions, excursions, etc. The authors study the components of discourse (participants of communicative events, the chronotope, pre- communicative, communicative and post-communicative phases) and its several classifications. The special attention is drawn to the addressee factor in formal educational communication and its explication in the conversational situation. The leading approach to the study of this problem is the discourse that allows to consider issues of preparation, carrying out and introspection of the organization of the educational space in the kindergarten in a way that meets the normative requirements of the federal state educational standard of pre-school education. The requirements of the basic educational program and, in general, the socio-cultural context, in which the child lives and is brought up, are also relevant. The discourse approach is the basis of the proposed communicative event. The result is a model of communication with children of preschool age during the educational situations on the basis of the discourse approach. The materials of the paper are of practical value to the organization of educational process in kindergartens. This data can also be used as a basis for the organization of educational activities in establishments of optional education. It is advisable to include the specifics of organizing the educational discourse in the curricula of pre- school teachers training.